Job stressors during remote work for Peruvian and Colombian teachers - Santa-Cruz-Espinoza, Henry (2025)
The teaching work was one of the most affected in terms of the changes suffered in their working conditions, during the Covid-19 pandemic. These effects have been even greater in Latin America, due to the shortcomings of developing countries. The objective of this study was to comparatively describe the experiences during remote work of Peruvian and Colombian teachers. The study was cross-sectional with a comparative design and it was developed in a non-probabilistic sample of 504 teachers (362 Peruvians and 142 Colombians). The scale of teaching stressors in times of pandemic, and a sociodemographic record, which were administered online, were used. The data were analyzed with Student's t-test and Hedges' G as a measure of effect. It was found that labor stressors do not differ according to sex; however, significant differences were identified in the stressors Work environment and workload, Use of new technologies and Organizational aspect of the educational institution, by country. These findings suggest a greater negative impact of stressors on teachers who were hit hardest by the pandemic.